7, 12‐Dihydrobenzo[de]indolo[3, 2‐b]quinoline: Unique Reactivity and Redox Interconversion. Issue 30 (8th August 2022) - Fujimoto, Keisuke; Sasaki, Kentaro; Yamagishi, Shota; Inuzuka, Toshiyasu; Sanada, Kazutaka; Sakamoto, Masami; Takahashi, Masaki
Abstract: Acetyl‐substituted 7, 12‐dihydrobenzo[ de ]indolo[3, 2‐ b ]quinoline was developed as a N ‐substituted polycyclic heteroaromatic molecule via Pd‐catalyzed cyclo‐isomerization of an alkyne precursor, followed by intramolecular Goldberg amination. This compound showed unique reactivity, notably, base‐mediated deacylative oxygenation and photo‐Fries rearrangement. A series of products exhibited characteristic electronic properties based on the redox state of the corresponding nitrogen atoms. The photo‐rearranged product, which possesses a 1, 2‐diaminoethene substructure, akin to the redox functionality of the natural flavin adenine dinucleotide, underwent reversible interconversion with the corresponding oxidized form. The efficient stabilization of the highly electron‐rich 7, 12‐dihydrobenzo[ de ]indolo[3, 2‐ b ]quinoline skeleton was ascribed to the electron‐withdrawing effect, intramolecular hydrogen bonding of the acetyl group, and local aromatic stabilization in the indole moiety. Abstract : Acetyl‐substituted 7, 12‐dihydrobenzo[ de ]indolo[3, 2‐ b ]quinoline was synthesized as a new nitrogen‐substituted polycyclic heteroaromatic compound with unique reactivities, namely, base‐mediated deacylative oxygenation and photo‐Fries rearrangement. The photorearranged product underwent reversible redox interconversion with the corresponding oxidized form with a significant change in the optical properties.